2014
DOI: 10.1146/annurev-physiol-021113-170408
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Acute Inflammation in the Lung

Abstract: Acute inflammation in the lung is essential to health. So too is its resolution. In response to invading microbes, noxious stimuli or tissue injury, an acute inflammatory response is mounted to protect the host. To limit inflammation and prevent collateral injury of healthy, uninvolved tissue, the lung orchestrates the formation of specialized pro-resolving mediators, specifically lipoxins, resolvins, protectins and maresins. These immunoresolvents are agonists for resolution that interact with specific recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
236
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(240 citation statements)
references
References 148 publications
2
236
1
1
Order By: Relevance
“…These results have important clinical implications for patients with ARDS including transfused, critically ill patients. Platelet depletion is impractical, as is aspirin therapy in many critically ill patients, but treatment with ATL, or perhaps other anti-inflammatory and proresolving mediators, 44 is an attractive approach. Further, the measurement of LPA in patients with ARDS and other critical illnesses could be a useful biomarker of inflammation and could be measured serially to assess therapeutic responses to treatment with pro-resolving lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…These results have important clinical implications for patients with ARDS including transfused, critically ill patients. Platelet depletion is impractical, as is aspirin therapy in many critically ill patients, but treatment with ATL, or perhaps other anti-inflammatory and proresolving mediators, 44 is an attractive approach. Further, the measurement of LPA in patients with ARDS and other critical illnesses could be a useful biomarker of inflammation and could be measured serially to assess therapeutic responses to treatment with pro-resolving lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis of LXA 4 has been established at sites of lung inflammation in the upper and lower airways and the vasculature (26,27). In response to lung inflammation, airway epithelial cells 15-LOX-derived 15S-hydroxyeicosatetraenoic acid can be transformed by neutrophil 5-LOX to an unstable epoxytetraene intermediate that is converted by enzymatic hydrolysis to LXA 4 and LXB 4 (15). LXA 4 binds specifically and reversibly to ALX/FPR2, a G protein-coupled receptor, with a K d of ∼0.5 nM (15,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In response to lung inflammation, airway epithelial cells 15-LOX-derived 15S-hydroxyeicosatetraenoic acid can be transformed by neutrophil 5-LOX to an unstable epoxytetraene intermediate that is converted by enzymatic hydrolysis to LXA 4 and LXB 4 (15). LXA 4 binds specifically and reversibly to ALX/FPR2, a G protein-coupled receptor, with a K d of ∼0.5 nM (15,28,29). In the present study, we found that both human MSCs and human AT II cells express biosynthetic enzymes and receptors for LXA 4 We have previously reported that clinical-grade human MSCs restored alveolar fluid clearance to a normal level and decreased inflammation in ex vivo human lungs injured with live E. coli bacteria (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations